Pengaruh Pemberdayaan Sikap Kerja dan Lingkungan Kerja terhadap Kinerja Pegawai Sekretariat DPRD Kabupaten Padang Lawas - Jhon Arief; Annisafitri annisafitri; Reza Affandi; Ahadiluly Ambiar (Manajemen dan Bisnis, 2022)
Problem of this study is how influence of empowerment on employee’s performance. How influence of work attitude  on employee’s performance. How influence work environment on employee’s performance. How influence of  empowerment, work attitude  and  work environment on employee’s performance. The purpose of this study to determine and analyze the effect of   empowerment on employee’s performance. Determine and analyze the effect of work attitude  on employee’s performance. Determine and analyze the effect of  work environment on employee’s performance. Determine and analyze the effect of empowerment, work attitude  and  work environment on employee’s performance. Sample in the study is 36  employee’s. Data analysis techniques used in this study is descriptive analyze and multiple linear regression analysis. The results of the study indicate empowerment variable has a positive and significant effect on employee’s performance. Work attitude  variable has a positive and significant effect on employee’s performance.  Work environment variable has a positive and significant effect on employee’s performance.    Empowerment, work attitude  and  work environment variable’s has a positive and significant effect on employee’s performance.